Online supervision in a professional doctorate in education: Cultivating relational trust within learning alliances. Issue 6 (2nd November 2021) - Jacobsen, Michele; Friesen, Sharon; Becker, Sandra
ABSTRACT: In this case study research, we examine online supervision and engagements in a blended education doctorate (EdD) programme through a lens of relational trust. Interviews with supervisors and EdD graduates enabled us to examine practices and strategies used to cultivate relationships and learning alliances that supported doctoral candidates in conducting research and dissertation writing. We explored opportunities and challenges in fostering effective supervisory relationships online. Five enabling factors for cultivating effective online supervisory relationships address programme design, supervisors' roles and responsibilities, and doctoral students' experiences. Establishing relational trust and learning alliances in early and ongoing engagements in programme through to culminating milestones was vital for effective student-supervisor relationships.